Health-related quality of life: chronic kidney disease patients in Riau - Ferdy Firmansyah; Tiara Tri Agustini (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2021)
Chronic Kidney Disease (CKD) can have an impact on quality of life which affects physical, mental health, functional status, and independence. The high prevalence of CKD will have an impact on the quality of life. The purpose of this study was to see the effect of the characteristics of CKD patients on the utility index score and to determine the dimensional correlation to the utility value measured using the SF-6D questionnaire. The study was conducted with an observational approach using a cross-sectional design in the CKD population in the city of Pekanbaru. The SF-6D questionnaire was administered to 122 patients to measure utility index scores. The difference in utility index scores based on patient characteristics was tested using Mann Whitney and Kruskal Wallis, while the correlation between domains and utility scores was used Pearson Correlation 0.61 ± 0.07. Score utility measured using the SF-6D instrument can distinguish utility values ​​based on education and comorbidities. There is a strong correlation (> 0.797) between vitality and mental domains with the SF-6D utility index.